Continuous EEG monitoring in Kenyan children with non-traumatic coma - Gwer, S; Idro, R; Fegan, G; Chengo, E; Garrashi, H; White, S; Kirkham, F; Newton, C (2012)
Background: The aim of this study was to describe the EEG and clinical profi le of seizures in children with non-traumatic coma, compare seizure detection by clinical observations with that by continuous EEG, and relate EEG features to outcome. Methods: This prospective observational study was conducted at the paediatric high dependency unit of Kilifi District Hospital, Kenya. Children aged 9 months to 13 years presenting with acute coma were monitored by EEG for 72 h or until they regained consciousness or died. Poor outcome was defi ned as death or gross motor defi cits at discharge. Results: 82 children (median age 2.8 (IQR 2.0-3.9) years) were recruited. An initial medium EEG amplitude (100-300 mV) was associated with less risk of poor outcome compared to low amplitude (≤100 mV) (OR 0.2, 95% CI 0.1 to 0.7; p<0.01). 363 seizures in 28 (34%) children were observed: 240 (66%) were electrographic and 112 (31%) electroclinical. In 16 (20%) children, electrographic seizures were the only seizure types detected. The majority (63%) of electroclinical seizures had focal clinical features but appeared as generalised (79%) or focal with secondary generalisation (14%) on EEG. Occurrence of any seizure or status epilepticus during monitoring was associated with poor outcome (OR 3.2, 95% CI 1.2 to 8.7; p=0.02 and OR 4.5, 95% CI 1.3 to 15.3; p<0.01, respectively). Conclusion: Initial EEG background amplitude is prognostic in paediatric non-traumatic coma. Clinical observations do not detect two out of three seizures. Seizures and status epilepticus after admission are associated with poor outcome.